Game theory evolving a problem-centered introduction to modeling strategic interaction - Gintis, Herbert (Princeton University Press, 2009)
This revised edition contains new material & shows students how to apply game theory to model human behaviour in ways that reflect the special nature of sociality & individuality. It continues its in-depth look at cooperation in teams, agent-based simulations, experimental economics, & the evolution & diffusion of preferences.